Towards development of a malaria diagnostic: Generation, screening and validation of novel aptamers recognising Plasmodium falciparum lactate dehydrogenase - Frith, Kelly-Anne (Rhodes University, Faculty of Science, Biotechnology Innovation Centre, 2020)
Malaria, caused by infection with the Plasmodium parasite, is one of the leading causes of death in under-developed countries. Early detection is crucial for the effective treatment of malaria, particularly in cases where infection is due to Plasmodium falciparum. There is, therefore, an enduring need for portable, sensitive, reliable, accurate, durable, self-validating and cost-effective techniques for the rapid detection of malaria. Moreover, there is a demand to distinguish between various infectious species causing malaria. Research in the area of malarial biomarkers has identified a unique, species-specific, epitope of P. falciparum lactate dehydrogenase (PfLDH), enhancing prospects for the development of diagnostics capable of identifying the species causing malarial infection. In recent years, improvements have been made towards the development of rapid diagnostic tests for detecting malarial biomarkers. Owing to their low cost, ease of labeling, and high thermal stability (relative to antibodies), the development and synthesis of aptamers that target the malarial lactate dehydrogenase represents one of the key innovations in the field of rapid diagnostics for malaria. This study explored the generation of aptamers that specifically target P. falciparum. Two sets of aptamers with diagnostically-supportive functions were generated independently, through parallel SELEX of recombinantly-expressed, full-length Plasmodium falciparum lactate dehydrogenase (rPfLDH), and an oligopeptide comprising the P. falciparum-specific epitope on lactate dehydrogenase (LDHp). The latter offers a promising solution for generating aptamers capable of binding with high specificity to P. falciparum. In this work, an rLDH class of aptamers was generated when SELEX was performed using the full-length rPfLDH protein as the target and the LDHp class of aptamers was generated when SELEX was performed using the oligopeptide LDHp as a target. Aptamers were successfully generated through the process of SELEX (systematic evolution of ligands through exponential enrichment) following the study and application of several optimisation steps, particularly during the amplification stage of SELEX. Optimisation steps included the study of improvements in PCR conditions; role of surfactants (Triton-X), modifying the PCR clean-up protocol; and agarose gel excision. Structurally-relevant moieties with particular consensus sequences (GGTAG and GGCG) were found in aptamers both reported here and previously published, confirming their importance in recognition of the target. Novel moieties particular to this work (ATTAT and poly-A stretches) were identified. Clades of consensus sequences were identified in both the rLDH and LDHp groups of aptamers, where sequences in the rLDH clade did not show preferential binding to rPfLDH while those in the LDHp clade (particularly LDHp 3 and 18) were able to recognise and bind only LDHp. Of the 19 sequences returned from the parallel SELEX procedures for rPfLDH (11 sequences) and LDHp (8 sequences), six rPfLDH and all eight LDHp sequences underwent preliminary screening and those with low responses eliminated. Of the eight LDHp-targeting aptamer sequences, five were preliminarily shown to bind to LDHp, whereas only two rPfLDH-targeting sequences were shown to bind to the target (rLDH 4 and 7). To this small selection of rPfLDH oligonucleotide sequences, two more (rLDH 1 and 15) were chosen for further study based on their sequences, secondary and predicted tertiary conformations. Sequences chosen for further study were therefore: rLDH 1, 4, 7 and 15 in the rLDH class, and LDHp 1, 3, 11, 14 and 18 in the LDHp class. Binding properties of the aptamers towards their targets were investigated using enzyme-linked oligonucleotide assays (ELONA), fluorophore-linked oligonucleotide assays (FLONA), electromobility shift assays (EMSA), surface plasmon resonance (SPR), and GelRed dissociation assays, while applications towards aptasensors were explored using electrochemical impedance spectroscopy (EIS) and fluorescent microscopy. Some inconsistencies were seen for specific aptamer to target binding interactions using specific techniques; however, generally, binding to the targets was observed across the techniques assessed. These varied responses demonstrate the need to screen and validate aptamers using a variety of techniques and platforms not necessarily specific for the proposed application. From the aptamer binding screening studies using ELONA, the most promising aptamers generated were identified as LDHp 11, rLDH 4, rLDH 7 and rLDH 15. Aptamer rLDH 4, which was generated against rPfLDH, exhibited preferential and specific binding to the lactate dehydrogenase from P. falciparum, over the recombinantly-expressed lactate dehydrogenase from Plasmodium vivax (rPvLDH), albeit with lowered responses compared to LDHp 11 in ELONA and EMSA studies. However, in kinetic ELONA studies rLDH 4 showed binding to both rPfLDH and rPvLDH. Aptamer rLDH 7 showed high affinity for rPfLDH and rPvLDH in kinetic studies using ELONA. However, screening studies with ELONA indicates that aptamer rLDH 7 may not be suitable for diagnostic tests in serum samples given its non-specific binding to human serum albumin (HSA). Aptamer rLDH 15 exhibited species specificity for rPfLDH in screening studies using ELONA but showed affinity towards rPvLDH (albeit lower relative to its affinity for rPfLDH) in kinetic studies using ELONA. LDHp 11, generated against the PfLDH peptide, showed a clear preference for rPfLDH when compared to rPvLDH and other control proteins, in both sets of ELONA studies conducted, as well as EMSA, thus possessing a strong ability to identify the presence of Plasmodium falciparum owing to its generation against the species-specific epitope. While LDHp 1 demonstrated binding to plasmodial LDH in a flow-through system (SPR), so reiterating ELONA responses, it did not perform well in the remaining methodologies. Aptamers rLDH 1 and 15 and LDHp 3, 14 and 18 exhibited a mixed set of results throughout the target protein screening analyses and were, thus, not considered for selective binding in P. falciparum parasite bodies. In studies aimed at exploring biosensor assemblies utilising the developed aptamers, both rLDH 4 and LDHp 11, along with rLDH 7, LDHp 1 and pL1, demonstrated in situ binding to the native PfLDH in fluorescent microscopy. LDHp 11 exhibited FITC-based fluorescence equivalent to the anti-rPfLDHp IgY antibody in confocal fluorescent microscopy indicating superior binding to the native PfLDH compared to the remaining aptamers. An examination of electrochemical impedance as a platform for a biosensor assembly did not, in these studies, exhibit the required sensitivity using physiologically relevant concentrations of analyte expected for pLDH following infection with Plasmodium spp. Malstat/LDH activity was explored for application in a colorimetric aptasensor. A decrease in both rPfLDH and rPvLDH activity was observed following incubation with the tested aptamers, but rLDH 1, rLDH 7 and LDHp 14 did not exhibit similar decreases in rPvLDH activity. Aptamers rLDH 1, 4 and 7 and LDHp 11 and 14 were, therefore, not selected as candidates for LDH capture in LDH activity-based diagnostic devices for P. falciparum. The decreases in pLDH activity in the presence of aptamers could hold promise as direct or antagonistic malaria therapeutic agents. Preliminary studies on the application of aptamers as malaria therapeutic agents, while of interest, should be viewed with due caution given the challenges of aptamers reaching the intracellular native plasmodial LDH hosted within the red blood cells. In conclusion, this work has shown the ability of the LDHp 11 aptamer, generated in these studies, to selectively bind rPfLDH over rPvLDH, and to bind to the native PfLDH in fluorescent microscopy, indicating that this aptamer holds promise as a biorecognition element in malaria biosensors and other diagnostic devices for the detection, and differentiation, of P. falciparum and P. vivax. The use of a species-specific epitope of P. falciparum as a target in aptamer generation paves the way for similar such studies aimed at generating aptamers with species selectivity for other Plasmodium species.
Keywords: Plasmodium falciparum; Malaria -- Chemotherapy; Oligonucleotides; Lactate dehydrogenase; Biochemical markers; Systematic evolution of ligands through exponential enrichment (SELEX)